2020
DOI: 10.18502/ijm.v12i4.3936
|View full text |Cite
|
Sign up to set email alerts
|

The role of Chlamydia trachomatis in preterm delivery: a case-control study in Besat Hospital, Sanandaj, Iran (2018-2019)

Abstract: Background and Objectives: Preterm delivery is an important subject in gynecology, obstetrics and pediatrics. It is defined as regular uterine contractions every five to eight minutes or less, lasting for 30 seconds. It is associated with progressive changes in the cervix, resulting in delivery after 22 weeks and before 37 weeks of gestation. This study aimed to evaluate the role of Chlamydia trachomatis infection in women with preterm delivery. Materials and Methods: This case-control study was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, there is some inconsistency regarding the impact of C. trachomatis on sPTB. In a case-control study involving 75 Iranian women with sPTB, no significant association with C. trachomatis cervical infection was observed when compared with 75 women with term births (86). Nevertheless, women with cervical C. trachomatis infection who received antibiotic treatment had lower rates of pPROM, sPTB, and small-for-gestational-age infants compared with those who did not receive antibiotic treatment (87,88), providing insight into the role of C. trachomatis in promoting sPTB.…”
Section: Preterm Birth and Infectionmentioning
confidence: 99%
“…However, there is some inconsistency regarding the impact of C. trachomatis on sPTB. In a case-control study involving 75 Iranian women with sPTB, no significant association with C. trachomatis cervical infection was observed when compared with 75 women with term births (86). Nevertheless, women with cervical C. trachomatis infection who received antibiotic treatment had lower rates of pPROM, sPTB, and small-for-gestational-age infants compared with those who did not receive antibiotic treatment (87,88), providing insight into the role of C. trachomatis in promoting sPTB.…”
Section: Preterm Birth and Infectionmentioning
confidence: 99%
“…They used vaginal swab samples to perform the test and after conducting the test, they observed that 7 (9.33%) of the controls and 2 (2.67%) of the patient group participants were infected with C. trachomatis . Therefore, they did not find a relationship between the mentioned infections and spontaneous preterm delivery ( Ahmadi et al., 2020 ). Although the results of this study were similar to our research, the noteworthy point was the significant reduction of chlamydia infection and its zero prevalence in our study.…”
Section: Discussionmentioning
confidence: 93%